Research on behavior of underground pressure in shallow coal seam with three-face goaf working face - Yin, Wang; Bin, Zhao; Zhigang, Deng; Kun, Lv; Hongwei, Wang (Frontiers in Energy Research, 2022)
During the mining process of coal mines, coal pillars are often formed in the goaf on three sides, and the stress behavior of coal seams has a significant impact on the safety of coal mines. The upper part of panel 3104 of Xinwang Coal Mine is the room-pillar goaf of the 2# coal seam, and the lower part is the goaf of the 7# coal seam. The same coal seam is adjacent to the goaf of panel 3102. Therefore, there are hidden dangers for safe mining in panel 3104 affected by the goaf on three sides. Through FLAC3D numerical simulation, on-site Pasat-M detection, microseismic monitoring, and support resistance measurement, the stress distribution law of surrounding rock in working face is analyzed. The following conclusions are obtained. There are several high wave velocity stress concentration areas in coal body of 3104 working face. During the mining of the working face, the mining influence 90m in front of the working face began to spread to the area of the left coal pillar, and the vertical stress at the left coal pillar began to increase. Stress concentration appears in 0-20m strata at the top of 3# coal seam. At the top of 3# coal seam, the vertical stress concentration coefficient can reach 2 in the range of 4-12m. The influence range of 3104 working face mining advance can reach 200m. Under the influence of mining, a large number of microseismic events occurred at 160m above and 150m below 3# coal seam. This law has reference value for the mining strata behaviors of coal seam under similar conditions.